2018
DOI: 10.1002/chem.201802498
|View full text |Cite
|
Sign up to set email alerts
|

Reoptimization of the Organocatalyzed Double Aldol Domino Process to a Key Enal Intermediate and Its Application to the Total Synthesis of Δ12‐Prostaglandin J3

Abstract: Re‐investigation of the l‐proline catalyzed double aldol cascade dimerization of succinaldehyde for the synthesis of a key bicyclic enal intermediate, pertinent in the field of stereoselective prostaglandin synthesis, is reported. The yield of this process has been more than doubled, from 14 % to a 29 % isolated yield on a multi‐gram scale (32 % NMR yield), through conducting a detailed study of the reaction solvent, temperature, and concentration, as well as a catalyst screen. The synthetic utility of this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 39 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…[1,2] So far, there have been more than 20 drugs related to prostaglandins marketed, some of which, such as latanoprost, have become billion-dollar drugs. [5,6] Elegant contributions to the total synthesis of PGJ compounds have also been made by Nicolaou, Carreira, and Stoltz. [5,6] Elegant contributions to the total synthesis of PGJ compounds have also been made by Nicolaou, Carreira, and Stoltz.…”
mentioning
confidence: 99%
“…[1,2] So far, there have been more than 20 drugs related to prostaglandins marketed, some of which, such as latanoprost, have become billion-dollar drugs. [5,6] Elegant contributions to the total synthesis of PGJ compounds have also been made by Nicolaou, Carreira, and Stoltz. [5,6] Elegant contributions to the total synthesis of PGJ compounds have also been made by Nicolaou, Carreira, and Stoltz.…”
mentioning
confidence: 99%
“…In summary, we have developed a simple-yet-complex organocatalysed aldol dimerization of succinaldehyde that delivers enal 6 in 29 % yield, 99 : 1 e.r., and on decagram scale. [32] We have utilized this key intermediate in the total synthesis of a wide range of medicinally relevant prostaglandins, and in almost half the number of steps previously reported. [21,32,34,38] We have also been able to demonstrate the versatility of enal 6 by successfully applying it to the total synthesis of stable prostacyclin and thromboxane analogues, [42] again in considerably fewer steps.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve our process, we started a further reoptimization campaign, re-evaluating both aldol reaction steps in the enal synthesis. [32] Initial re-optimization studies (Table 2) demonstrated a slight increase in yield from standard conditions (14 %, entry 1) by switching the solvent from THF to acetonitrile (MeCN) (16 %, entry 2), and a further increase by diluting the concentration of the first aldol step (19 %, entry 3). However, at this stage we observed complications during purification of enal 6, where a drop in isolated yield was observed (19 % NMR yield !9% isolated yield) due to the formation of Scheme 12.…”
Section: Re-optimization Of the Organocatalysed Aldol To The Key Enalmentioning
confidence: 99%
See 2 more Smart Citations